Human Cytomegalovirus-Encoded G Protein-Coupled Receptor UL33 Facilitates Virus Dissemination via the Extracellular and Cell-to-Cell Route - van Senten, Jeffrey R. (Viruses, 2020)
Human cytomegalovirus (HCMV) encodes four G protein-coupled receptor (GPCR) homologs. Three of these receptors, UL78, US27 and US28, are known for their roles in HCMV dissemination and latency. Despite importance of its rodent orthologs for viral replication and pathogenesis, such a function is not reported for the HCMV-encoded GPCR UL33. Using the clinical HCMV strain Merlin, we show that UL33 facilitates both cell-associated and cell-free virus transmission. A UL33-deficient virus derivative revealed retarded virus spread, formation of less and smaller plaques, and reduced extracellular progeny during multi-cycle growth analysis in fibroblast cultures compared to parental virus. The growth of UL33-revertant, US28-deficient, and US28-revertant viruses were similar to parental virus under multistep growth conditions. UL33- and US28-deficient Merlin viruses impaired cell-associated virus spread to a similar degree. Thus, the growth defect displayed by the UL33-deficient virus but not the US28-deficient virus reflects UL33’s contribution to extracellular transmission. In conclusion, UL33 facilitates cell-associated and cell-free spread of the clinical HCMV strain Merlin in fibroblast cultures.